The application of expanded graphite fabricated by microwave method to eliminate organic dyes in aqueous solution. Issue 1 (1st January 2019) - Hoang, Ngoc Bich; Nguyen, Thi Thuong; Nguyen, Tien Sy; Bui, Thi Phuong Quynh; Bach, Long Giang
Abstract: Recently, organic contaminants from textile and dye industry have adversely affected on human's health and living things. Hence, the development of effective contaminated water treatment is one of the most crucial tasks. Expanded Graphite (EG) has been considered as efficient platforms to remove of organic dyes from aqueous solution due to its excellent performance. The main objective of the present work is to investigate adsorption behavior of methylene blue (MB) and Congo Red (CO) on exfoliated graphite fabricated using flake graphite from Yen Bai province. The exfoliation of graphite was carried out using potassium permanganate and perchloric acid as oxidant agent and anhydride acetic as intercalating agent via microwave-assisted technique. The properties of EG were characterized by X-ray diffraction, scanning electron microscopy, Fourier-transform infrared spectroscopy and nitrogen adsorption/desorption analysis. In batch adsorption experiments, various factors including initial dye concentration (50–600 ppm), adsorbent dosage (0.5–3 g/L), contact time (10–120 min) and pH of solution (4–10) were also studied. It is found that as-prepared EG provided high removal efficiency and fast adsorption rate for MB and CO. The maximum adsorption capacity of EG for CO and MB was found at 201.21 and 47.62 mg/g, respectively. These results demonstrate that the as-synthesized EG appears as an efficient and low-cost platform for remediation of colored effluents via adsorption route.